Effects of competition level on the centre forward role of men's water polo - Lupo, C.; Minganti, C.; Cortis, C.; Perroni, F.; Capranica, L.; Tessitore, A. (Journal of Sports Sciences, 2012)
This study aimed to compare specific technical and tactical indicators of the team and centre forward role of Euro League, and Italian Serie A1, Serie A2, and Serie B men's water polo club competitions. A notational analysis was performed on 21 water polo matches to evaluate the occurrence of technical and tactical team and centre forward indicators, highlighting differences among championships according to chi-square analyses. Differences emerged for Counterattack (P < 0.001) and Power-Play (P < 0.001) possessions, Even (P < 0.001; Euro League: 3 ± 1, Serie A1: 3 ± 2, Serie A2: 3 ± 2, Serie B: 6 ± 4) and Power-Play (P = 0.001) goals, and exclusions and penalties (P = 0.008) of the team during Even possessions. Relatively to the role analyses, effects emerged for perimeter players playing events (P = 0.049), as well as for centre forwards' goals (P = 0.007) and exclusions and penalties (P < 0.001; Euro League: 8 ± 1, Serie A1: 6 ± 2, Serie A2: 6 ± 2, Serie B: 3 ± 2) occurring at the end of Even possessions. Therefore, in Euro League, and Italian Serie A1 and Serie A2, teams perform a high occurrence of Power-Play possessions following up an exclusion, especially achieved by the centre forward during Even possessions, while, in Italian Serie B, goals were mostly scored during Even possessions, with a relevant contribution from the centre forward role.